Belajar dari Aktivis Perempuan Muda: Sebuah Cara Memengaruhi Kesadaran Politis Sejak Dini - Ikhaputri Widiantini; Retno Daru Dewi G. S. Putri (Yayasan Jurnal Perempuan, 2023)
This research emphasizes the importance of involving young women in various activism. Problems arise when young women are often considered immature to be involved in social and political movements. Apart from being supported by a patriarchal mindset that tends to subordinate women’s experience, there is an intersectional problem where young people need more knowledge to make changes. In fact, one way to encourage active representation of women in political space is to encourage involvement from a young age. This research explores the activism experiences of young women who influence their respective communities. Data was collected through Focus Group Discussion (FGD) and strengthened through literature studies. The data is managed using a political participation theory approach, as well as the influence of affect theory in digital activism. The findings in this research show that young women’s knowledge is just as essential in the political space. Their advocacy is full of the spirit of the times, so they can have a strong influence on other young women through the community they have built.